Transforming Urban Islamic Education: Principal Strategies for Fulfilling SDGs 4 on Quality Education - Nur Vambudi, Viky; Ali, Mohamad; Ali Mustofa, Triono; Ganapathy, Malini; Badat Alauddin, Muhammad (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to compare strategies and identify the impact of strategies implemented by the principals of Muhammadiyah Junior High School PK Kottabarat Surakarta and Muhammadiyah Al-Kautsar PK Sukoharjo Junior High School in improving the quality of education. Theoretical framework:  this research is based on Whetten & Cameron's theory of transformational leadership and Schultes' theory of facilitative leadership applied by principals. Literature review: A literature review includes literature on leadership, quality schools, and Islamic education. It is still found that existing studies focus only on general education without considering the religious dimension in Islamic education. Methods: data collection techniques using observation, interviews, and document studies, with credibility and dependability tests as data validity tests. Data analysis techniques consist of data reduction, data presentation, and data verification. Results: The results of the study showed that SMP Muhammadiyah PK Kottabarat Surakarta implemented a transformational model strategy, while SMP Muhammadiyah Al-Kautsar PK Sukoharjo focused more on a facilitative model. The two schools have similarities in their digitalization strategy, but differ in policies such as the standardization of prospective students and the handling of discipline of education personnel. The impact of this strategy at SMP Muhammadiyah PK Kottabarat Surakarta includes increasing public interest, school achievement, SBBI Award, and teacher welfare. Meanwhile, at Muhammadiyah Al-Kautsar PK Sukoharjo Junior High School, the impact can be seen in the increase in registrants, academic and non-academic achievements, and the progress of infrastructure. Implications: This research promotes the importance of transformational leadership in urban Islamic schools, highlighting its crucial role in improving education quality and aligning educational strategies with the achievement of SDG 4, while emphasizing the need for further studies on leadership models that integrate Islamic values in urban educational contexts. Novelty: The novelty of this research lies in the integration of the leadership strategies of urban Islamic school principals with the achievement of SDG 4, which is rarely discussed in the Islamic education literature.